(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Twenty five rice genotypes were used to study the genetic components, correlation and path coefficients during Aman season of 2011. Thirteen characters were studied to find out the suitable traits for the improvement of rice yield. Among these characters considerable correlation were observed. Correlation values of grain yield per square meter with plant height, number of tillers per hill, number of panicles per hill, panicle length, number of primary branches, number of filled grain per panicle, spikelet sterility (%), 1000 grain weight and days to flowering revealed that selection based on this traits could significantly be improved the grain yield of rice. Number of tillers per hill, number of panicles per hill, panicle length, number of filled grains per panicle, 1000-grain weight exhibited high direct effect coupled with significant positive correlation on grain yield indicating selection on the basis of these traits would enhanced yield potentiality of rice. The residual effect was found 0.179 which indicated that 82.10% of the variability was accounted for 13 yield and yield contributing traits included in the present study. Rest 17.90% variability might be controlled by other yield contributed traits that was not included in the present investigation. So direct selection based on these traits would be effective for improvement of these F4 materials